Care for Postpartum Depression: What Do Women and Their Partners Prefer?. Issue 2 (25th February 2015) - Feeley, Nancy; Bell, Linda; Hayton, Barbara; Zelkowitz, Phyllis; Carrier, Marie‐Eve
Abstract : Purpose: To compare the preferences of those who accept a mental health assessment and those who do not. Design and Methods: Thirty couples participated in a qualitative study. Nineteen couples accepted a mental health assessment and 11 declined. Findings: Acceptors wanted more contact with professionals. Decliners preferred support from their informal network, parental leave, and exercise. However, acceptors also cited these preferences. Practice Implications: Nurses should tailor care to couples' preferences, helping them identify and utilize preferred resources. Mental health care might be more acceptable to decliners if provided in obstetrical care.